KNOWLEDGE, ATTITUDE AND PRACTICES ABOUT COVID VACCINATION AMONG RURAL AND URBAN POPULATION - Nagoor Khadervali; Dudekula Raziya; Pichika Sasikala; Yamasani Bhavani; SK Zameer; S Govindu (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: In the current phase of widespread availability of safe and effective COVID-19 vaccines, the subsequent challenge lies in addressing vaccine hesitancy and dispelling prevalent myths surrounding vaccination. The aim and objective of this study are to investigate the knowledge, attitudes, and practices concerning COVID vaccination within both rural and urban populations. Material and Methods: The study employs a pre-designed semi-structured questionnaire as its primary tool, adopting a cross-sectional design. The targeted study population includes 250 individuals from both urban and rural areas within the vaccination age group. Inclusion criteria encompass individuals aged 20 and above who willingly participate, while exclusion criteria involve those who decline participation. Results: The study, with a mean participant age of 37.15±4.3 years, revealed an educational distribution where 57.8% were graduates. Notably, 69.6% of graduates were from urban areas, indicating significant urban-rural disparities. A male preponderance was observed, with higher proportions of females in rural and males in urban areas. Vaccination status showed that approximately 78.6% had received two doses, with higher unvaccinated individuals in urban areas. Urban regions exhibited higher knowledge levels, with 59.2% awareness of COVID-19 vaccine preparation and statistically significant awareness of three doses (40%) and variants (83.6%). Urban residents also displayed a strong belief (91.6%) that COVID vaccines were provided free of cost. Urban areas demonstrated proactive preventive behaviors, including adherence to precautions (87.6%) and booster doses (75.6%) after the second vaccine dose. In contrast, rural regions exhibited a lower readiness for vaccination, with 47.6% willingly receiving the vaccine. Conclusion: Overall, this study provides valuable insights into the dynamics of COVID-19-related factors in both urban and rural populations, offering a foundation for targeted interventions, policy adjustments, and further research endeavors.